2020
DOI: 10.1371/journal.pone.0228390
|View full text |Cite
|
Sign up to set email alerts
|

Real-world experiences: Efficacy and tolerability of pirfenidone in clinical practice

Abstract: BackgroundThe safety of pirfenidone on pulmonary fibrosis patients with other kinds of interstitial lung diseases (ILDs) in addition to idiopathic pulmonary fibrosis (IPF) is unknown. Furthermore, its effectiveness-related factors on IPF patients are not quite explored. MethodsA retrospective study, on patients prescribed pirfenidone for pulmonary fibrosis, was conducted to assess effectiveness on IPF patients and tolerability of all patients with lung fibrosis. The effectiveness of pirfenidone was tested on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 40 publications
4
26
1
1
Order By: Relevance
“…Our results are surprising as it appears patients with a normal BMI are at an increased risk of dying. However, this nding, alongside DLco as a predictor of mortality, is consistent with Fang et al's real world pirfenidone study [28]. We also noted that baseline BMI was a predictor of anti brotic discontinuation, which has been reported previously [29], with Kato et al [30] nding that low BMI increases the risk of experiencing nintedanib-associated gastrointestinal side effects.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are surprising as it appears patients with a normal BMI are at an increased risk of dying. However, this nding, alongside DLco as a predictor of mortality, is consistent with Fang et al's real world pirfenidone study [28]. We also noted that baseline BMI was a predictor of anti brotic discontinuation, which has been reported previously [29], with Kato et al [30] nding that low BMI increases the risk of experiencing nintedanib-associated gastrointestinal side effects.…”
Section: Discussionsupporting
confidence: 91%
“…However, this finding, alongside DLco as a predictor of mortality, is consistent with Fang et al ’s real-world pirfenidone study. 28 We also noted that baseline BMI was a predictor of antifibrotic discontinuation, which has been reported previously, 29 with Kato et al 30 finding that low BMI increases the risk of experiencing nintedanib-associated gastrointestinal side effects.…”
Section: Discussionsupporting
confidence: 80%
“…Finally, the factors which might affect the efficacy of pirfenidone were not analyzed. One study reported that IPF patients with a >25 kg/m 2 in body mass index (BMI) or a >30% in DLco had a higher progression-free survival rate, 28 but similar analyses were not performed in our study due to the limited quality and information of patients.…”
Section: Discussionmentioning
confidence: 96%